2016
DOI: 10.1093/mnras/stw1081
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the accretion rate in thin discs around binary black holes

Abstract: We present three-dimensional Smoothed Particle Hydrodynamics (SPH) simulations investigating the dependence of the accretion rate on the disc thickness around an equal-mass, circular black hole binary system. We find that for thick/hot discs, with H/R 0.1, the binary torque does not prevent the gas from penetrating the cavity formed in the disc by the binary (in line with previous investigations). The situation drastically changes for thinner discs, in this case the mass accretion rate is suppressed, such that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
77
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 81 publications
(153 reference statements)
18
77
1
Order By: Relevance
“…3) and develops an eccentric cavity similar to those found in previous circumbinary disc simulations (e.g. Farris et al 2014;D'Orazio et al 2016;Ragusa et al 2016) and used by Ragusa et al (2017) to explain dust horseshoes. The spiral arms appear fixed in relation to the binary orbit, but superimposed on this is a precessing overdensity which precesses on a timescale of 2-3 orbital periods, as found by Dunhill, Cuadra & Dougados (2015).…”
Section: Spiralssupporting
confidence: 65%
See 2 more Smart Citations
“…3) and develops an eccentric cavity similar to those found in previous circumbinary disc simulations (e.g. Farris et al 2014;D'Orazio et al 2016;Ragusa et al 2016) and used by Ragusa et al (2017) to explain dust horseshoes. The spiral arms appear fixed in relation to the binary orbit, but superimposed on this is a precessing overdensity which precesses on a timescale of 2-3 orbital periods, as found by Dunhill, Cuadra & Dougados (2015).…”
Section: Spiralssupporting
confidence: 65%
“…Recently, Ragusa et al (2017) showed that central binaries can produce both rings and horseshoes in dust emission. Indeed, eccentricities around the cavity edge are a common feature in hydrodynamical simulations of circumbinary discs (Kley & Dirksen 2006;Farris et al 2014;Ragusa et al 2016). Ragusa et al (2017) showed that more massive companions produce progressively more asymmetric structures, with simulated ALMA observations closely matching observed discs.…”
Section: Observational Constraintsmentioning
confidence: 77%
See 1 more Smart Citation
“…The ratio of the former to the latter characterizes the extent to which gravitational torques from the binary suppress or enhance accretion. Previous studies have reported values of this ratio both smaller than unity (e.g., MacFadyen & Milosavljević 2008;Ragusa et al 2016), and greater than unity (e.g., Farris et al 2014). In considering these claims, it is necessary to make a distinction between discs whose outer edges spread freely, and those whose outer regions are supplied with mass at a steady rate (e.g., due to an infalling envelope).…”
Section: Introductionmentioning
confidence: 99%
“…Recent results of Ragusa et al (2016) suggest that for colder disks with lower aspect ratio < h r 0.1 the binary accretion rateṀ b actually drops compared to˙¥ M . This would imply that mass accumulates more efficiently near the binary in colder disks, making situation discussed in Section 3.2.1 possible.…”
Section: Binary Accretion Ratementioning
confidence: 99%